Athletic cognitive motivation and its relationship to perform some duties within the defensive formations of the region for handball players aged (15-17) years - Ibtisam Saleem (الرياضة المعاصرة)
The study aimed to identify the athletic cognitive motivation and its relationship in the performance of some duties within the defensive formations of the region for handball players aged 15-17 years, and the researcher used the descriptive approach to suit the nature of the research problem on a sample of (24) players from the National Center for Talent Care Sports handball of the Ministry of Youth and Sports / Baghdad for the season (2018-2019) and ages (15-17) years and the total number (34) player, and the researcher used the scale of sports knowledge motivation prepared by Al-Badrani (2012), and conducting a handball match, and used The appropriate statistical means for data processing are: